1991
DOI: 10.1159/000177660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Ribose on Muscle Metabolism during Bicycle Ergometer in AMPD-Deficient Patients

Abstract: Three patients with AMP deaminase deficiency (AMPD deficiency) performed exercise on a bicycle ergometer with increasing work load without and with administration of ribose (3 g p.o. every 10 min, beginning 1 h before exercise until the end). The patients performed exercise until heart rate was 200 minus age. Maximum capacity was not increased by administration of ribose, but postexertional muscle stiffness and cramps disappeared almost completely in 2 of 3 AMPD-deficient patients. Plasma concentrations of lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…GPLC transports fatty acids to the mitochondria for oxidation, CoQ10 is essential for adenosine-5 0 -triphosphate (ATP) production as a cofactor in the mitochondrial electron transport chain, and D-ribose is an intergral structural component of ATP. These three nutrients have been demonstrated to increase exercise capacity in humans [100][101][102][103] and equids [58,104], presumably by stimulating ATP production and recovery while supporting ATP energy substrates at the same time [105]. Daily ribose supplementation (0.07 g/kg BW, twice daily) for 14 days in the diet of exercising geldings resulted in lower blood ammonia-N and plasma lactic acid during recovery after a standardized exercise test.…”
Section: Discussionmentioning
confidence: 99%
“…GPLC transports fatty acids to the mitochondria for oxidation, CoQ10 is essential for adenosine-5 0 -triphosphate (ATP) production as a cofactor in the mitochondrial electron transport chain, and D-ribose is an intergral structural component of ATP. These three nutrients have been demonstrated to increase exercise capacity in humans [100][101][102][103] and equids [58,104], presumably by stimulating ATP production and recovery while supporting ATP energy substrates at the same time [105]. Daily ribose supplementation (0.07 g/kg BW, twice daily) for 14 days in the diet of exercising geldings resulted in lower blood ammonia-N and plasma lactic acid during recovery after a standardized exercise test.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been observed that both patients and mice with myositis acquire a deficiency of the muscle specific enzyme AMPD1 [4], [6]. Second, there are published case reports describing the successful treatment of muscle weakness and fatigue with D-ribose in patients with congenital deficiency of AMPD1 enzyme activity [9], [10], [11]. Finally, an examination of the metabolites within the muscle tissue of myositis mice revealed a deficiency in metabolites related to the internal production of D-ribose.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that D-ribose could ameliorate muscle weakness by serving as an energy source [10], [11], but there is little research that specifically addresses this topic. While it is known that D-ribose is well absorbed in the small intestine [23] and that pentose sugars can be reversibly converted into hexose sugars, most sources focus on the production of ribose from glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, ingesting supplemental doses of ribose may increase adenine nucleotide salvage and de novo synthesis, which would preserve the adenine nucleotide pool, increase cellular concentrations of adenosine diphosphate and adenosine triphosphate (ATP), and allow rapid restoration of cellular energy (1,5,16,18,22,27,28,35). In clinical populations, ribose has been implicated as an energy-providing supplement that may alter cardiac muscle function, reduce muscle cramping, and increase exercise tolerance (11,12,17,32,36). Therefore, adding ribose to the carbohydrate-protein repletion drink may enhance the muscle recovery and the benefits of endurance training.…”
Section: Introductionmentioning
confidence: 99%